Child Tracking System using Blynk and GPS Technology - Nasaruddin, Norashikin; Mohd Zin, Rosnah (Evolution in Electrical and Electronic Engineering, 2023)
Child missing or kidnapping is a significant issue affecting many families globally. A child tracking system is a technological solution providing access to real-time information on the whereabouts of children through SMS notifications and Blynk. In this project, the child's location is tracked using a GPS module and then sent to a NodeMCU ESP8266 microcontroller. The microcontroller processes the data, and the location data is then analyzed and displayed in real-time on the Blynk app. This project also features an SMS notification system that sends an alert message to the parent's phone to track the coordinates of the child in Google Maps. The ESP8266 establishes a connection and provides GPS data to the Blynk application when it is inside the 45-meter Wi-Fi range. But the ESP8266 switches to GSM mode if the child goes outside of this range and loses Wi-Fi connectivity. In GSM mode, it continuously monitors the location of the child by sending coordinates through SMS to the parent's phone every minute. The project achieved all its objectives and provided an easy approach for parents to keep track of their children's whereabouts and react quickly in a state of emergency.